2008
DOI: 10.1021/es7021413
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Structural Characterization of Dissolved Organic Matter from the Deep Ocean by FTICR-MS, Including Hydrophilic Nitrogenous Organic Molecules

Abstract: Dissolved organic matter isolated from the deep Atlantic Ocean and fractionated into a so-called hydrophobic (HPO) fraction and a very hydrophilic (HPI) fraction was analyzed for the first time by Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS) to resolve the molecular species, to determine their exact masses, and to calculate their molecular formulas. The elemental composition of about 300 molecules was identified. Those in the HPO fraction (14C age of 5100 year) are very similar to muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 31 publications
10
90
1
1
Order By: Relevance
“…The weak anionexchange resin diethylaminoethyl (DEAE)-cellulose could extract highly oxygenated compounds in natural water [19,26], but the contents of aliphatic and aromatic compounds were reduced. In particular, nitrogenous molecules in DOM are hard to isolate from aqueous samples on hydrophobic stationary phases due to their hydrophilic and zwitterionic characters [23]. Here, by using the SPE-SE procedure, the number of identified nitrogenous molecules (S/N !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak anionexchange resin diethylaminoethyl (DEAE)-cellulose could extract highly oxygenated compounds in natural water [19,26], but the contents of aliphatic and aromatic compounds were reduced. In particular, nitrogenous molecules in DOM are hard to isolate from aqueous samples on hydrophobic stationary phases due to their hydrophilic and zwitterionic characters [23]. Here, by using the SPE-SE procedure, the number of identified nitrogenous molecules (S/N !…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have observed that a great number of compounds in DOM such as highly oxygenated tannin-like molecules [22,23], nitrogenous compounds with high hydrophilic character [23], and fatty-acid-like molecules [24] are preferentially lost during the single-step SPE procedure for a variety of SPE sorbents, such as XAD, C 18 and PPL [19,22e26]. To solve this problem, combinations of different isolation methods such as dialysis and SPE [24], ultrafiltration and SPE [25] or SPE with a combination of different sorbents [19,23,26] have been attempted recently in order to obtain a more accurate molecular representation of DOM. Nevertheless, the combination of different isolation methods is highly laborious, time-consuming, and hard to optimize and standardize.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that, in this study, C 18 solid phase extraction (SPE) was used to isolate and concentrate the analyte from samples and for desalting because ESI FT-ICR MS analysis requires salt-free samples. Only molecules that can be adsorbed on C 18 and desorbed by an organic solvent were analyzed by mass spectrometry. Highly hydrophilic (incomplete adsorption) or highly hydrophobic (incomplete desorption) molecules were not considered.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In the last decade, ultrahigh-resolution Fourier Transform Ion-Cyclotron Resonance Mass Spectrometry (FT-ICR MS) has extended the analytical window for organic matter characterization due to its capacity for resolving thousands of constituents with individual elemental compositions in complex DOM mixtures. FT-ICR MS provided insights into the sources of DOM in various environments (Kim et al, 2004;Koch et al, 2005;Dittmar and Koch, 2006;Hertkorn et al, 2006;Tremblay et al, 2007;Reemtsma et al, 2008;Schmidt et al, 2009;Bhatia et al, 2010;D'Andrilli et al, 2010;Lechtenfeld et al, 2013;Roth et al, 2013) and it revealed transformation of DOM related to microbial processes (Kim et al, 2006;Longnecker and Kujawinski, 2011;Schmidt et al, 2011), fungal degradation (Grinhut et al, 2011), and photochemical alteration (Kujawinski et al, 2004;Gonsior et al, 2009).…”
Section: Introductionmentioning
confidence: 99%